2016
DOI: 10.1007/s10071-016-0972-7
|View full text |Cite
|
Sign up to set email alerts
|

Caching at a distance: a cache protection strategy in Eurasian jays

Abstract: A fundamental question about the complexity of corvid social cognition is whether behaviours exhibited when caching in front of potential pilferers represent specific attempts to prevent cache loss (cache protection hypothesis) or whether they are by-products of other behaviours (by-product hypothesis). Here, we demonstrate that Eurasian jays preferentially cache at a distance when observed by conspecifics. This preference for a ‘far’ location could be either a by-product of a general preference for caching at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 20 publications
0
16
2
Order By: Relevance
“…Previous experiments have indicated that Eurasian jays do attend to social context in caching and mate provisioning (Shaw & Clayton, 2012; Shaw & Clayton, 2013; Ostojić et al, 2013; Shaw & Clayton, 2014; Ostojić et al, 2014; Legg, Ostojić & Clayton, 2016). It is therefore still possible that jays use social information, but not for copying others’ choices, as none of the previous experiments required the birds to copy a demonstrator.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous experiments have indicated that Eurasian jays do attend to social context in caching and mate provisioning (Shaw & Clayton, 2012; Shaw & Clayton, 2013; Ostojić et al, 2013; Shaw & Clayton, 2014; Ostojić et al, 2014; Legg, Ostojić & Clayton, 2016). It is therefore still possible that jays use social information, but not for copying others’ choices, as none of the previous experiments required the birds to copy a demonstrator.…”
Section: Discussionmentioning
confidence: 99%
“…They also adjust their behaviour appropriately depending on whether they are caching or pilfering (Shaw & Clayton, 2014), and whether they compete with a dominant or subordinate (Shaw & Clayton, 2012). Furthermore, they prefer to cache out-of-sight behind an opaque barrier and at a distance when observed by conspecifics (Legg & Clayton, 2014; Legg, Ostojić & Clayton, 2016). During the breeding season, males are attentive to which foods their mates might prefer based on how much of which foods she has already eaten (Ostojić et al, 2013; Ostojić et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Previous experiments have indicated that Eurasian jays do attend to social context in caching and mate provisioning (Shaw & Clayton, 2012;Ostojić et al, 2013;Ostojić et al, 2014;Legg, Ostojić & Clayton, 2016). It is therefore still possible that jays use social information, but not for copying others' choices, as none of the previous experiments required the birds to copy a demonstrator.…”
Section: Manuscript To Be Reviewedmentioning
confidence: 98%
“…Previous studies have indicated that Eurasian jays do attend to social context in caching and mate provisioning (Shaw & Clayton, 2012;Ostojić et al, 2013;Ostojić et al, 2014;Legg, Ostojić & Clayton, 2016). It is therefore still possible that jays use social information, but not for copying others' choices, as none of the previous studies required the birds to copy a demonstrator.…”
Section: Discussionmentioning
confidence: 97%
“…They also adjust their behaviour appropriately depending on whether they are caching or pilfering , and whether they compete with a dominant or subordinate (Shaw & Clayton 2012). Furthermore, they prefer to cache out-of-sight behind an opaque barrier and at a distance when observed by conspecifics Legg, Ostojić & Clayton, 2016). During the breeding season, males are attentive to which foods their mates might prefer based on how much of which foods she has already eaten (Ostojić et al, 2013;Ostojić et al, 2014).…”
Section: Introductionmentioning
confidence: 99%